PENINGKATAN KETERAMPILAN BERBICARA DALAM BERMAIN DRAMA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE-OUTSIDE CIRCLE - Dewi, Candra (Lecturer at the Faculty of Education, University of Muhammadiyah Malang, 2017)
ABSTRAKTujuan penelitian ini adalah untuk meningkatkan kemampuan berbicara melalui penerapan model pembelajaran kooperatif tipe inside outside circle (IOC) pada siswa kelas 4 Sekolah Dasar Negeri Pintu Kecamatan Jenangan Kabupaten Ponorogo. Variabel yang menjadi sasaran perubahan dalam penelitian ini adalah kemampuan berbicara, sedangkan variabel tindakan yang digunakan dalam penelitian ini adalah penerapan model pembelajaran kooperatiftipe inside outside circle (IOC).Bentuk penelitian ini adalah penelitian tindakan kelas sebanyak 2 siklus. Tiap siklus terdiri dari 4 tahapan yaitu perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subyek penelitian adalah siswa kelas 4 Sekolah Dasar Negeri Pintu Kecamatan Jenangan Kabupaten Ponorogo yang berjumlah 20 siswa. Teknik pengumpulan data menggunakan observasi, wawancara, tes dan dokumentasi. Teknik analisis data yang digunakan adalah model analisis interaktif yang mempunyai tiga buah komponen yaitu reduksi data, penyajian data dan penarikan simpulan.Berdasarkan hasil penelitian dapat disimpulkan bahwa ada peningkatan kemampuan berbicara dalam kegiatan bermain peran setelah diadakan tindakan kelas dengan menerapkan model pembelajarankooperatiftipe inside outside circle (IOC).Kata Kunci : Keterampilan Berbicara, Drama, Inside-Outside CircleÂ Abstract :The purpose of this research is to improve the ability to talk through the implementation of cooperative learning model inside outside circle (IOC) in the 4th grade students of State Elementary School District of Jenangan Doors Ponorogo. Variables that were subjected to a change in this study is the ability to speak, while the action variable used in this research is the application of cooperative learning model inside outside circle (IOC). This research is a form of action research as much as 2 cycles. Each cycle consists of four phases: planning, action, observation and reflection. Subjects were students in grade 4 Doors Public Elementary School District of Jenangan Ponorogo totaling 20 students. Data collection technique used observation, interview, test and documentation. Data analysis technique used is an interactive model that has three components: data reduction, data presentation, and drawing conclusions. Based on the results of this study concluded that there is an increased ability to speak after having a class action by implementing cooperative learning model inside outside circle (IOC). It can be shown by the increasing ability of students before and after the action.The purpose of this research is to improve the ability to talk through the implementation of cooperative learning model inside outside circle (IOC) in the 4th grade students of State Elementary School District of Jenangan Doors Ponorogo. Variables that were subjected to a change in this study is the ability to speak, while the action variable used in this research is the application of cooperative learning model inside outside circle (IOC). This research is a form of action research as much as 2 cycles. Each cycle consists of four phases: planning, action, observation and reflection. Subjects were students in grade 4 Doors Public Elementary School District of Jenangan Ponorogo totaling 20 students. Data collection technique used observation, interview, test and documentation. Data analysis technique used is an interactive model that has three components: data reduction, data presentation, and drawing conclusions. Based on the results of this study concluded that there is an increased ability to speak after having a class action by implementing cooperative learning model inside outside circle (IOC). Â Keywords :Speaking Skills, Drama, Inside-Outside Circle.